PENTINGNYA PENDIDIKAN DAN KETERAMPILAN DALAM MENINGKATKAN ETOS KERJA PEGAWAI DI KANTOR KECAMATAN ULUGAWO KABUPATEN NIAS - Gori, Saforius; Eliagus Telaumbanua (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
Ulugawo District Office, Nias Regency. Until now, it tends to be ignored about the level of education of an employee at the Ulugawo District Office, Nias Regency, and has not fully supported the improvement of employee performance where the lack of employee discretion in carrying out their duties, decision-making authority is also still limited, and there is a lack of feedback. The purpose of the study was to determine the importance of education in improving employee work ethic at the Ulugawo District Office, Nias Regency.To determine the importance of skills in improving employee work ethic at the Ulugawo District Office, Nias Regency.To determine the importance of education and skills in improving employee ethos at the Ulugawo District Office, Nias Regency. The method used is qualitative research method. The results of the study With the existence of education and qualified skills can help improve the work ethic of employees at the Ulugawo Sub-District Office. higher education usually provides broader knowledge and a better understanding of the duties and responsibilities of employees. Qualified skills can also enable employees to perform their duties more efficiently and effectively.